Legacy and emerging contaminants in flamingos' chicks' blood from the Ebro Delta Natural Park. (January 2023) - Dulsat-Masvidal, Maria; Bertolero, Albert; Mateo, Rafael; Lacorte, Silvia
Abstract: The Ebro Delta is a wetland of international importance for waterbird conservation but severally affected by intensive agriculture, toxic waste discharges from a past chloro-alkali industry and affluence of tourism. The discharge of contaminants associated to these activities pose waterbirds breeding in the Ebro Delta at risk. The aim of this study is to evaluate the exposure of 91 emerging and legacy micropollutants in flamingo chicks ( Phoenicopterus roseus ), an emblematic species of the area. Fifty chicks of 45–60 days were captured, biometric parameters measured and whole blood collected. Compounds analyzed included perfluoroalkyl substances (PFASs), pharmaceuticals, organophosphate esters (OPEs), in-use pesticides, polychlorinated biphenyls (PCBs), organochlorine pesticides (OCs), and polycyclic aromatic hydrocarbons (PAHs). The results indicate a multi-exposure of flamingo's chicks from a very young age. PFASs were the most ubiquitous compounds with ∑PFASs ranging from 9.34 to 576 ng/mL, being PFOA, PFOS and PFHxS detected in all samples. ∑PAHs ranged from 0.19 to 423 ng/mL, ∑PCBs from 0.5 to 15.6 ng/mL and ∑OCs from 1.35 to 37.8 ng/mL. Pharmaceuticals, OPEs and in-use pesticides were not detected. The flamingo's filtering behavior on mud and maternal ovo-transference are the more likely routes of exposure of organic micropollutants to flamingos' chicks. The reported levels of micropollutants were not associated with any alteration in the body condition of chicks. This is the first study to describe flamingos chicks' exposure to multiple contaminants, highlighting the importance of biomonitoring for wildlife conservation and biodiversity preservation. Graphical abstract: Image 1 Highlights: Flamingos are exposed to organic micropollutants from a very young age. Unexpected high PFASs concentrations were found in flamingos' blood. PFOA, PFOS and PFHxS were detected in all individuals due to recent exposure. PAHs and organochlorine pesticides were also prevalent but at low concentrations. Micropollutants were not associated with alterations in body indexes.